Pengembangan Kemampuan Bahasa Anak Usia Dini melalui Cerita Dongeng Si Kancil dan Buaya - Marsya Riski; Syamsiah Depalina Siregar (Jurnal Pendidikan dan Humaniora Rumbio, 2025)
This study aims to develop early childhood language skills through the folktale Si Kancil dan Buaya (The Clever Mouse Deer and the Crocodile). The folktale was chosen as a learning medium due to its educational, imaginative, and engaging values for children. The research was conducted at an early childhood education institution in Panyabungan using a descriptive qualitative approach. The subjects were group B children aged 5–6 years. Data collection techniques included observation, interviews, and documentation. The results revealed that storytelling using Si Kancil dan Buaya significantly improved children's language abilities, particularly in vocabulary development, story comprehension, retelling skills, and speaking confidence. The folktale served as an effective stimulus in fostering children's interest in language, stimulating imagination, and reinforcing social-emotional skills through the moral messages conveyed. Thus, the story of Si Kancil dan Buaya proves to be a relevant and effective medium for developing language skills in early childhood.